Vertiports: The Infrastructure Backbone of Advanced Air Mobility—A Review - Paola Di Mascio; Giulia Del Serrone; Laura Moretti (Eng)
Technological innovation toward electrification and digitalization is revolutionizing aviation, paving the way for new aeronautical paradigms and novel modes to transport goods and people in urban and regional environments. Advanced Air Mobility (AAM) leverages vertical and digital mobility, driven by safe, quiet, sustainable, and cost-effective electric vertical takeoff and landing (VTOL) aircraft. A key enabler of this transformation is the development of vertiports—dedicated infrastructure designed for VTOL operations. Vertiports are pivotal in integrating AAM into multimodal transport networks, ensuring seamless connectivity with existing urban and regional transportation systems. Their design, placement, and operational framework are central to the success of AAM, influencing urban accessibility, safety, and public acceptance. These facilities should accommodate passenger and cargo operations, incorporating charging stations, takeoff and landing areas, and optimized traffic management systems. Public and private sectors are investing in vertiports, shaping the regulatory and technological landscape for widespread adoption. As cities prepare for the future of aerial mobility, vertiports will be the cornerstone of sustainable, efficient, and scalable air transportation.